Analisis Kualitas Jaringan Intra Pemerintah Diskominfo Kabupaten Soppeng Pada Layanan Internet Kantor Kecamatan - Khairullah Hafid; Muh Rifaldi Al Mursyid; Asmini Asmini; Sukriadi Sukriadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study evaluates the Quality of Service (QoS) of the intra-government network managed by Diskominfo Soppeng Regency, focusing on internet services provided to its sub-district offices. The research methodology involves analyzing key QoS parameters—bandwidth, throughput, latency, jitter, and packet loss—to assess the network's overall performance and reliability. The findings indicate that the network's quality is good; however, it reveals areas for technical improvement. While functionally adequate, these results suggest that the network has not yet reached its full potential. Consequently, these findings provide a foundation for the local government, particularly Diskominfo, to plan strategic infrastructure upgrades and capacity expansion. The goal is to optimize service delivery, ensuring the network can effectively and efficiently support inter-agency data communication requirements.